Perspective of Public Financial Management: The Role of the Ministry of Finance and the Supreme Audit Agency in Indonesia - Fadjar Tri Sakti; Ahmad Rizki Mubarok; Dena Irawan; Hani Anas Setia; Zaidiah Nur Afifah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The Ministry of Finance (Kemenkeu) and the Financial Audit Agency (BPK) have a very important role in Indonesia's central government, especially in managing and supervising state finances. The Ministry of Finance has a central role in managing state finances, including planning, budgeting and financial reporting. Meanwhile, the Financial Audit Agency is responsible for conducting audits of state financial management to ensure accountability and transparency. This research aims to analyze the role of the Ministry of Finance and the Financial Audit Agency in central government. The research method used is descriptive analysis, namely by collecting data from various sources related to the role and function of the Ministry of Finance and the Financial Audit Agency. The results of the analysis show that the Ministry of Finance and the Supreme Audit Agency have a very important role in maintaining state finances and encouraging efficiency and transparency in public financial management. This research provides a better understanding of how the two institutions work together to manage state finances effectively